Multi-objective optimization design of recycled aggregate concrete mixture proportions based on machine learning and NSGA-II algorithm - Fan, Mengtian; Li, Yue; Shen, Jiale; Jin, Kaikai; Shi, Junjie (Advances in engineering software (1992), 2024)
•A database on compressive strength of recycled aggregate concrete is built up.•The compressive strength prediction models with high accuracy are constructed.•The multi-objective optimization design of recycled aggregate concrete mixture proportions based on machine learning and NSGA-II algorithm is carried out.•The influence factors on compressive strength of recycled aggregate concrete are analyzed. This paper employs Support Vector Regression (SVR), Random Forest Regression (RF), Gradient Boosting (GB), and Extreme Gradient Boosting (XGB) algorithms to establish the compressive strength prediction models for Recycled Aggregate Concrete (RAC) and analyze the influence of ten inputs on RAC compressive strength. Combined with the best prediction model, the Non-dominated Sorting Genetic Algorithm Ⅱ (NSGA-II) is applied for multi-objective optimization of mixture proportions in RAC addressing cost, carbon emissions, and compressive strength as key objectives. The results demonstrate that the RAC compressive strength prediction model using the GB algorithm exhibits the highest accuracy, with the R2 value of 0.99 for the training set and 0.85 for the testing set. Feature importance and SHAP analysis reveal that cement and water contents are the primary factors affecting the compressive strength of RAC. Among the three mineral admixtures including Silica Fume (SF), Fly Ash (FA), and Ground Granulated Blast Furnace Slag (GGBFS), SF exhibits superior improvement in the compressive strength of RAC compared to FA and GGBFS. Partial dependency plot analysis indicates that concrete strength remains unaffected by recycled coarse aggregate content within the range of 0 to 300 kg/m3. Pareto fronts of a tri-objective mixture optimization problem for RAC are successfully obtained through the GB model combined with the NSGA-II algorithm, which can guide the optimization of RAC preparation.